Serapan Karbondioksida Vegetasi Hutan Rawa Gambut Berdasarkan Tingkat Pertumbuhan: Vegetation Uptake of Carbon Dioxide on Peat Swamp Forests Based on The Growth Rate - Ajun Junaedi; Nisfiatul Hidayat; Moh Rizal; Esti Munthe (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2022)
This study aims to identify the type composition and estimate the potential for biomass and carbon deposits as well as carbon dioxide (CO2) uptake of peat swamp forest vegetation based on the growth rates (seedling, sapling, pole, tree). The estimation of potential deposits of vegetation biomass is calculated by destructive and non-destructive methods. The potential for carbon impedance is calculated using the formula Bof National Standardization (2011) and CO2 absorption with the IPCC formula (2006). The results showed that the number of vegetation types found was 44 types from 25 families. Stake-level vegetation is the most common type found compared to seedlings, poles, and trees. Tree-level vegetation is dominated by Cratoxylon arborescent BI, Combretocarpus rotundatus pole level, and Stemonurus secundiflorus Blume stake level., the seedling level of Anacolosa frutescens. The potential for biomass, carbon deposits, and CO2 uptake of peat swamp forest vegetation is 179.976 tons/ha; 84.588 tons C/ha; 310.442 tons CO2/ha, respectively. Tree-level vegetation has the highest deposits of biomass and carbon as well as CO2 uptake compared to seedling, sapling, and pole levels. Youth-level vegetation (seedlings, sapling, pole) in peat swamp forests has great potential in storing biomass, carbon, and CO2 uptake in the long term. Keywords: biomass, carbon, carbon dioxide uptake, peat swamp forest, vegetation